Electronic — microscopic study of the ultrastructure of the chorioretinal complex of rats in dynamics after introduction of the increased dose of methanol (Ukrainian Journal of Ophthalmology, 2026)
Introduction. A wide use of methanol and its availability increase probability of casual or its chronic influence on the human organism. Therefore, it is important to study its mechanisms for the person as well as other alive creatures. Purpose of the investigation. To study the influence of methanol on ultrastructure of the chorioretinal complex (CRC): (choriocapillaries (CC) — pigment epithelium of the retina (PER) — photoreceptor cells (PC) of the retina) of white rats. Material and methods. Electronic- microscopic changes in the elements of CRC of white rats in dynamics (1—14 day) after unitary intraabdominal introduction of methanol in the dose of 2.5 g/kg of body weight were investigated. Results and discussion. It is shown that the pathological process has a wavy course: on the 1st day the basic ultrastructural changes were revealed in CC and PER. In PER they consisted in alteration of mitochondria and canaliculi of the smooth endoplasmic net, in focal destruction of the plasmatic membranes, especially of the apical areas of cells. In PER cells signs of the endocellular compensatory-regenerative processes were revealed to the greatest degree on the 3rd day. However, damages of the structures were aggravated on the 7th — 14th day. Conclusions. Toxic effect of methanol in the dose of 2.5 g/kg of the body weight on CRC structures is manifested for a long time. Cells of PER react to the applied influence to the greatest degree
Keywords: chorioretinal complex; ultrastructure; choriocapillaries; pigment epithelium of the retina; photore-ceptor cells